Anthropometric and Hematological Profile of some selected Ethiopian Premier League Male Soccer Players in the Final Competitive Season - Ayichew Abay; Wondiye Aychiluhim (Türk Spor ve Egzersiz Dergisi)
The purpose of the study to determine anthropometric and hematological profile of some selected Ethiopian premier league male soccer players according to playing position. Descriptive cross-sectional study was employed on purposely selected twenty eighty premier league soccer players from (14) Sidama Coffee and from (14) Hawassa Town soccer club from all positions (GK, DF, MD, SK). Anthropometric, physiological performance and seventeen hematological parameters (WBC, RBC, Lymph, HGB, HCT, MCV, MCH, MCHC, PLT, RDW-CV, RDW-SD, PLT, MPV, PDW, PCT, P-LCC, and P-LCR) were measured. The obtained quantitative data was analyzed by one way analysis of variance (ANOVA) (p lt;0.05) with the help of SPSS version 20.00 software. The study found mean scores of anthropometric, performance and hematological parameter among soccer players. Further a statistically significant change was observed is only WBC, RBC and MCH hematological variables were observed when compared among the different playing positions (Goalkeepers, defenders, midfielders and attackers). It was concluded that there is no significant difference in anthropometric, physiological and hematological variables except (WBC, RBC and MCH) soccer players between playing position, although the values of the measured hematological parameters fell within the reference range. Regular monitoring of the hematological parameters is fundamental for the identification of a health status and related optimal performances by sport medicine specialist, nutritionist, trainers and selection of adequate training intensity by trainers. From a practical point of view, the clinician has to take into account not only age, but also training status of individuals when evaluating their blood tests.